2017
DOI: 10.3389/fneur.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Dependent Changes in Dura Mater Microvasculature Add New Insights to the Pathogenesis of Headache

Abstract: The pathogenesis of headaches is a matter of ongoing discussion of two major theories describing it either as a vascular phenomenon resulting from vasodilation or primarily as a neurogenic process accompanied by secondary vasodilation associated with sterile neurogenic inflammation. While summarizing current views on neurogenic and vascular origins of headache, this mini review adds new insights regarding how smooth muscle-free microvascular networks, discovered within dura mater connective tissue stroma (prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…A drop in estrogen may cause an increased sensitivity to prostaglandins and a release of neuropeptides such as CGRP, substance P and neurokinins which could result in neurogenic inflammation [17]. This physiological response provokes alterations in the microvasculature of the dura mater, changes in calcium and magnesium concentrations, and an imbalance in serotonin and dopamine concentrations [17, 21, 50]. Estrogen withdrawal might lead to an increased oxidative stress in the cells [51].…”
Section: Resultsmentioning
confidence: 99%
“…A drop in estrogen may cause an increased sensitivity to prostaglandins and a release of neuropeptides such as CGRP, substance P and neurokinins which could result in neurogenic inflammation [17]. This physiological response provokes alterations in the microvasculature of the dura mater, changes in calcium and magnesium concentrations, and an imbalance in serotonin and dopamine concentrations [17, 21, 50]. Estrogen withdrawal might lead to an increased oxidative stress in the cells [51].…”
Section: Resultsmentioning
confidence: 99%
“…Positioned inside the intracranial cavity, an indistensible closed space, the dura mater not only protects intracranial structures, but also represents the critical site for CSF turnover (Dandy, 1929; Papaiconomou et al, 2004; Mack et al, 2009) and the main route for the brain venous/CSF outflow. Further, given these anatomical traits and location, there is a reason to believe that alterations within vascular networks into, and particularly out of the CNS within the cranial dura mater are significant, yet unappreciated initiators and/or contributors to a myriad neurological disorders including migraine (Glinskii et al, 2017), dural aneurysms (Baltsavias et al, 2015a, b) leading to a higher risk of intracranial hemorrhage, dural sinus/cerebral vein thrombosis (Baltsavias et al, 2015a, c), multiple sclerosis (Louveau et al, 2016), and Alzheimer’s disease (Louveau et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This early inflammatory process is mediated by sensory neurotransmitters released from the trigeminal neurons [ 35 ] also supplying sensory innervation to both vascular and stromal dural territories [ 36 , 37 ]. We speculate that early dural responses to corneal injury, which require separate investigation, most likely involve a cascade of events within highly innervated and vascularized dura mater connective tissue and depends on the local distribution of meningeal perivascular or stromal nociceptors [ 38 ]. It has been reported that CGRP (calcitonin gene-related peptide) or SP (substance P) neuropeptide release from activated nociceptors is associated with vasodilation, plasma protein leakage, extravasation of leukocytes, tissue swelling, mast cell activation [ 39 ] and augmented mechanosensitivity [ 40 ] leading to the impaired meningeal vascular integrity.…”
Section: Discussionmentioning
confidence: 99%